Examining the factor structure, reliability, and validity of the main outcome measure used in mentalization‐based therapy skills training. Issue 1 (15th February 2021) - Polnay, Adam; McIntosh, Lindsey G.; Burnett, Aileen; Williams, Andrea; Cahill, Catherine; Wilkinson, Peter; Mohammad, Fiona; Patrick, Jon
Abstract: Background and Aims: Multiple national guidelines stress the importance for clinicians to possess good therapeutic skills for working with patients with significant relational difficulties (who may receive a diagnosis of personality disorder). Training clinicians in mentalization‐based treatment skills (MBT‐S) is one approach to address this. The main outcome measure used in MBT‐S studies is the Knowledge and Application of MBT Questionnaire (KAMQ). However, an absence of research into the properties and validity of the KAMQ has limited the methodological quality of MBT‐S evaluations so far. The aim of this study was therefore to investigate the factor structure, internal consistency, reliability, and validity of the KAMQ. Methods: Using an existing multiprofessional sample of 217 clinicians from 2014 to 2016, we undertook exploratory factor analysis to determine the factor structure and internal consistency of the KAMQ. Convergent validity of the measure with the Attitudes to Personality Disorder Questionnaire (APDQ) was assessed in a subset of this dataset where both questionnaires had been administered ( n = 92). Additionally, by recruiting a new sample of 70 clinicians, we assessed the measure's test‐retest reliability. Results: Factor analysis found three factors underlying 17 of the 20 KAMQ items, relating to therapeutic skills in mentalizing, beliefs about applying MBT in practice, and specific MBT knowledge. The KAMQ was revised following the factor analysis to form the KAMQ‐2 with 17 items. Internal consistency ( α = .85, 95% confidence interval [CI] = 0.80‐0.89) and test‐retest reliability (ICC = 0.84, 95% CI = 0.73‐0.91) were good. In correlation analyses, the KAMQ‐2 showed convergent validity with the main factor from the APDQ ( n = 48; r s = 0.39, P  < .01). Conclusion: The KAMQ‐2 provides a short, reliable self‐report instrument which probes clinicians' knowledge about mentalizing skills, and beliefs about using these. There was preliminary evidence for validity. The properties of the KAMQ‐2 mean that more robust evaluation and development of MBT‐S is now possible.